Identical Parallel Machine Scheduling to Minimize Makespan Using Suggested Algorithm Method at XYZ Company - Naura Maisazahra; Murni Dwi Astuti; Murman Dwi Prasetio (School of Industrial and System Engineering, Telkom University, 2022)
XYZ company produce the various shape of motor spare parts product. The company has three identical parallel spot welding machines that use a random method of production scheduling, based on machine capacity without any sequence of jobs, and only use daily production targets given to operators. Based on the data, the actual scheduling of the machines has a very large completion time difference between each machine, or the machine loading is uneven. As a result, the makespan becomes longer with a value of 440000 seconds (26 days). This research aims to minimize the existing makespan by giving proposed scheduling, using the suggested algorithm method, which has a small number of iterations and has an optimal result. The method begins with the longest processing time sequence rule which is used as the upper bound for the first iteration, then continued to calculate the lower bound and machine workload. The calculation stops at the 15th iteration because the completion time value exceeds the lower and upper bound so that the optimal scheduling taken is scheduled in the 14th iteration with a makespan value of 914412 seconds (16 days). The proposed scheduling can minimize the makespan from the actual schedule by 38%.